Jugamos a resolver problemas de combinación 2 - Ramírez Caballero, Esther (2019)
The session entitled We play to solve combination problems 2, was developed in the area of mathematics taking into account the problem-solving approach whose competence solves quantity problems, from the necessary resources such as capabilities translates quantities into numerical expressions , communicates your understanding of numbers and operations, uses estimation and calculation strategies and procedures, argues statements about numerical relationships and operations; It has been possible to achieve the performance establishes relationships between data and one or more actions of adding, removing, moving forward, backward, putting together, separating, comparing and equalizing quantities, and transforming them into numerical expressions (model) of addition or subtraction with natural numbers of Up to two figures._x000D_ In the development of the session, motivational and challenging activities were applied that encouraged the achievement of active participation through play and teamwork._x000D_ The pedagogical processes such as motivation and exploration of previous knowledge, problematization, construction of learning and information processing, evaluation and transfer in the didactic processes of the area were taken into account._x000D_ The learning strategies were in accordance with the interests and needs of the students of second grade of primary education.